Characterization of noncalcified coronary plaques and identification of culprit lesions in patients with acute coronary syndrome by 64-slice computed tomography - Kitagawa, Toshiro; Yamamoto, Hideya; Horiguchi, Jun; Ohhashi, Norihiko; Tadehara, Futoshi; Shokawa, Tomoki; Dohi, Yoshihiro; Kunita, Eiji; Utsunomiya, Hiroto; Kohno, Nobuoki; Kihara, Yasuki (JACC. Cardiovascular imaging, 2009)
We sought to characterize noncalcified coronary atherosclerotic plaques in culprit and remote coronary atherosclerotic lesions in patients with acute coronary syndrome (ACS) with 64-slice computed tomography (CT). Lower CT density, positive remodeling, and adjacent spotty coronary calcium are characteristic vessel changes in unstable coronary plaques. Of 147 consecutive patients who underwent contrast-enhanced 64-slice CT examination for coronary artery visualization, 101 (ACS; n = 21, non-ACS; n = 80) having 228 noncalcified coronary atherosclerotic plaques (NCPs) were studied. Each NCP detected within the vessel wall was evaluated by determining minimum CT density, vascular remodeling index (RI), and morphology of adjacent calcium deposits. The CT visualized more NCPs in ACS patients (65 lesions, 3.1 +/- 1.2/patient) than in non-ACS patients (163 lesions, 2.0 +/- 1.1/patient). Minimum CT density (24 +/- 22 vs. 42 +/- 29 Hounsfield units [HU], p < 0.01), RI (1.14 +/- 0.18 vs. 1.08 +/- 0.19, p = 0.02), and frequency of adjacent spotty calcium of NCPs (60% vs. 38%, p < 0.01) were significantly different between ACS and non-ACS patients. Frequency of NCPs with minimum CT density <40 HU, RI >1.05, and adjacent spotty calcium was approximately 2-fold higher in the ACS group than in the non-ACS group (43% vs. 22%, p < 0.01). In the ACS group, only RI was significantly different between 21 culprit and 44 nonculprit lesions (1.26 +/- 0.16 vs. 1.09 +/- 0.17, p < 0.01), and a larger RI (> or = 1.23) was independently related to the culprit lesions (odds ratio: 12.3; 95% confidential interval: 2.9 to 68.7, p < 0.01), but there was a substantial overlap of the distribution of RI values in these 2 groups of lesions. Sixty-four-slice CT angiography demonstrates a higher prevalence of NCPs with vulnerable characteristics in patients with ACS as compared with stable clinical presentation.